Sex, Sin and Marriage: Feminists in Patriarchal Culture, Religious Values and the Struggle for the Equality - Nuriyati Samatan, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Sex, Sin and Marriage: Feminists in Patriarchal Culture, Religious Values and the Struggle for the Equality, is a study conducted on the novel Eks Parasit Lajang by Justina Ayu Utami. The approach of this research is qualitative with Critical Analysis of Frankfrut School method through four levels of analysis: Totality, Awareness, Alienation and Criticism. The results of this study show that in the level of totality, Ayu Utami sees the problems experienced by character A as a problem that not only comes from herself, but also from her family who embrace Patriarchal culture, religious values, and also the values come from the society. In the level of Awareness, Ayu Utami sees that the world is constructed by men, and marriage as a mean of legitimizing power (patriarchal); in the level of Alienation, Ayu Utami is alienated from the concept of the church which is considered problematic; about herself and her sexual organs; about the values of women and marriage, until she decides to "take off the Cross's necklace" and ends up "deciding not to have any religion". In the Criticism level, Ayu Utami criticizes her religionâ€™s "Holy Book", Patriarchal culture and also criticizes on the State regulations which she considers unfair especially in marriage arrangement as well as the society values which are considered confining and disadvantaging women, but not for men.Â